Cistanche tubulosa phenylethanoid glycosides induce apoptosis in H22 hepatocellular carcinoma cells through both extrinsic and intrinsic signaling pathways - Pengfei Yuan; Jinyu Li; Adila Aipire; Yi Yang; Lijie Xia; Xinhui Wang; Yijie Li; Jinyao Li (BMC, 2018)
Abstract Background Cistanche tubulosa (Schenk) R. Wight is a traditional Chinese medicine that parasitizes the roots of the Tamarix plant and has been used to treat male impotence, sterility, body weakness, and as a tonic. However, its antitumor effect on hepatocellular carcinoma is still elusive. Here, we investigated the antitumor effect of C. tubulosa phenylethanoid glycosides (CTPG) on H22 hepatocellular carcinoma cells both in vitro and in vivo and its mechanisms. Methods The morphology, viability, apoptosis, cell cycle and mitochondrial membrane potential (Δψm) of H22 cells were analyzed by inverted microscopy, MTT assay and flow cytometry, respectively. The expression and activation of proteins in apoptosis pathway were detected by Western blot. The in vivo antitumor effect was evaluated in tumor mouse model established using male Kunming mice. Results CTPG treatment significantly suppressed H22 cell growth in a dose- and time-dependent manner, which was correlated with the increased apoptosis and cell cycle arrest at G0/G1 and G2/M phases. Moreover, the chromosomal condensation was observed in CTPG-treated H22 cells. CTPG treatment significantly increased Bax/Bcl-2 ratio, reduced Δψm and enhanced the release of cytochrome c. The levels of cleaved caspase-8 and caspase-9 in both extrinsic and intrinsic signaling pathways were significantly increased that sequentially activated caspase-7 and -3 to cleave PARP. Finally, CTPG inhibited the growth of H22 cells in mice and improved the survival rate of tumor mice. Conclusions These results suggested that CTPG suppressed H22 cell growth through both extrinsic and intrinsic apoptosis pathways.